STUDY FOR BETTER BLOOD PRESSURE AND CARDIOVASCULAR RISK CONTROL IN A RURAL AREA OF RWANDA. (April 2021) - Muggli, Franco; Parati, Gianfranco; Suter, Paolo; Bianchetti, Mario; Muvunyi, Bienvenu; Ntaganda, Evariste
Abstract: Objective: Also in Sub-Saharan Africa (SSA), the burden of hypertension and related cardiovascular (CV) complications is an health threat. Between October and November 2017 blood pressure (BP) was assessed in 372 subjects (>18y) at the Health Centre of Nyamyumba, a village of the rural District of Nyaruguru (Rwanda), where the MABAWA Association is active for more than 15 years as an integrated development project (www.mabawa.org ). BP was determined by mean of oscillometric device. Systolic BP 140mmHg or more was detected in 136 subjects (68 females and 54 males). Hence we decided to perform a local study with the aim to exactly determine the prevalence of hypertension and to improve its control. Design and method: Phase 1 of the study aims to assess the incidence of hypertension and other CV risk factors. Phase 2 will focus the control of hypertension and associated CV risk factors with the aim of providing improved CV protection. The aim will be achieved by establishing a clinical consultation module which will be culturally and risk pattern adapted. The protocol of the project has the approval of the Rwanda National Ethic Committee and the endorsement of the World Hypertension League. Subjects living in Nyamyumba will be visited at home by instructed health care providers and BP will be measured using a validated oscillometric device (OMRON HEM-7322U) according to a standardized protocol. Subjects with elevated BP will be asked to participate to the project. Those with confirmed hypertension will undergo a clinical examination including anthropometric measurements, electrocardiogram and laboratory test (blood count, creatinine, potassium, total-/, HDL-/ and LDL-cholesterol, triglyceride, HbA1c and microalbuminuria). Finally, they will be taught in a culturally adapted way to understand the risk associated with high BP and start appropriate life style and medical intervention. Results: expected for 2021 Conclusions: High BP likely affects millions of people in Africa. It is the most important cause of heart disease and stroke. Only few SSA countries have a clear hypertension management strategy. Our purpose is to identify practical and feasible solution to improve control of BP and associated risk factors in Rwanda.